2014
DOI: 10.1111/imm.12240
|View full text |Cite
|
Sign up to set email alerts
|

Basophils as a primary inducer of the T helper type 2 immunity in ovalbumin‐induced allergic airway inflammation

Abstract: SummaryAntigen-induced allergic airway inflammation is mediated by T helper type 2 (Th2) cells and their cytokines, but the mechanism that initiates the Th2 immunity is not fully understood. Recent studies show that basophils play important roles in initiating Th2 immunity in some inflammatory models. Here we explored the role of basophils in ovalbumin (OVA) -induced airway allergic inflammation in BALB/c mice. We found that OVA sensitization and challenge resulted in a significant increase in the amount of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Numerous studies have demonstrated that basophils not only play crucial roles in the effector phase, but also critically participate in the initiation of Th2-centered immune responses (7)(8)(9)(10)(11). Using an ovalbumin (OVA)-induced allergic airway inflammation mouse model, we previously showed that basophils acted as a primary inducer of the Th2 immunity, evident by increased OVA-specific immunoglobulin E (OVA-sIgE) and IL-4 levels both in serum and bronchial alveolar lavage fluid (BALF), and increased proportion of Th2 cells in the spleen after transfusion of lung basophils derived from OVA-challenged mice into wild-type (WT) mice (12). We also found that pulmonary basophils were capable of antigen uptake, expressed an array of molecular markers such as CD40, CD80/86, and MHC II and released high levels of IL-4 following OVA sensitization and challenge.…”
Section: Asthma Is Characterized By Increased Airway Submucosal Infilmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have demonstrated that basophils not only play crucial roles in the effector phase, but also critically participate in the initiation of Th2-centered immune responses (7)(8)(9)(10)(11). Using an ovalbumin (OVA)-induced allergic airway inflammation mouse model, we previously showed that basophils acted as a primary inducer of the Th2 immunity, evident by increased OVA-specific immunoglobulin E (OVA-sIgE) and IL-4 levels both in serum and bronchial alveolar lavage fluid (BALF), and increased proportion of Th2 cells in the spleen after transfusion of lung basophils derived from OVA-challenged mice into wild-type (WT) mice (12). We also found that pulmonary basophils were capable of antigen uptake, expressed an array of molecular markers such as CD40, CD80/86, and MHC II and released high levels of IL-4 following OVA sensitization and challenge.…”
Section: Asthma Is Characterized By Increased Airway Submucosal Infilmentioning
confidence: 99%
“…For the initiation of Th2 cells, BM-Bas (2.5 ϫ 10 5 per well) and naïve CD4 ϩ T cells (5 ϫ 10 5 per well) were seeded in 96-well plates in RPMI 1640 complete medium in the presence of rIL-2 (20 U/ml, R&D Systems), rIL-3 (30 ng/ml), DNP-OVA (100 g/ml, Biosearch Technologies, Novato) and anti-DNP IgE (10 g/ml, Sigma-Aldrich) for 5 days (7,12). For some experiments, anti-mouse CD252 (20 g/ml, OX40L blocking Ab, ␣OX40L, eBioscience) was added to the cultures.…”
Section: Mice-ox40mentioning
confidence: 99%
See 3 more Smart Citations